Gender Contest In Public Office Study At North Sulawesi Provincial Government - Jenny N. H. Paomey; Khasan Effendy; Deti Mulyati; Prio Teguh (International Journal of Economics Development Research (IJEDR), 2023)
Gender mainstreaming in the field of governance amidst gender inequality due to the construction of people's thinking triggered by gender stereotypes which is a barrier factor for women to actively participate in community development and empowerment. This study uses descriptive qualitative methods with the intention of revealing how gender contestation is in public office in the Provincial Government of North Sulawesi. The analysis of this study uses the Liberal Feminist theory of Gender. The results of this study reveal that gender contestation in public office is still not optimal due to uneven competence between men and women, lack of access and opportunities given to women, as well as internal factors of women who do not develop self-competence, supported by the absence of rules that regulates the representation of women in public office. In addition, the regional head's commitment has not been optimally implemented in the policy for determining candidates for high-ranking officials because it is still influenced by patriarchal culture in the organizational culture so that in determining the filling of the JPT, they still use the conventional model which should use a non-gender model that is competent which is recommended to be implemented in filling out the JPT in the Province. North Sulawesi so that gender mainstreaming can run in all levels of government to accelerate the development of human resources.